Pengaruh Pemanfaatan Taman Sekolah Sebagai Sumber Belajar Terhadap Hasil Belajar Pada Pelajaran Ipa Kelas V SDN Sridamai. - Mutia Hanifah mutia; Yasir Arafat; Kiki Aryaningrum (Publikasi Indonesia, 2022)
The effect of the use of school gardens as a learning resource on learning outcomes in the fifth grade science lesson at SDN Sripeace. The purpose of this study was to determine the effect of using the school garden as a learning resource on learning outcomes in the fifth grade science lesson at SDN Sripeace. The method used is an experimental method using the Pre-Experimental Design (Nondesign) approach, the form of design used is One-Group Pretest-Posttest. The population and sample of this study were all fifth grade students of SDN Sripeace with a total of 11 students. The data collection technique is done by means of tests. The data analysis technique used was Descriptive Statistics and Inferential Statistics. In this study using the normality test and get the results for the pretest X2 count (9.325) < X2 table (9.487). The results of the posttest data on the use of school gardens as a learning resource on learning outcomes in the fifth grade science lesson at Sripeace Elementary School obtained X2 count (0.277) < X2 table (9.487) so it can be concluded that the data are normally distributed. kthen the results of the t-test are known that the t-count value (6.074) > t-table (2.262) can be concluded that the t-count is greater than the t-table. So in the research in this study it can be concluded that there is an influence on the use of school gardens as learning resources on learning outcomes in science lessons for class V SDN Sripeace.